THE EFFECT OF PROFITABILITY, INSTITUTIONAL OWNERSHIP, AND ENVIRONMENTAL PERFORMANCE ON SUSTAINABILITY REPORT DISCLOSURE - Ni Luh Intan Lestari; I Gusti Ayu Nyoman Budiasih (Adisam Publisher, 2026)
Sustainability report disclosure has become a crucial aspect of corporate reporting practices as a form of accountability to stakeholders. Sustainability report disclosure, as an indicator of corporate social responsibility, is increasingly gaining attention from stakeholders. This study aims to obtain empirical evidence regarding the effect of profitability, institutional ownership, and environmental performance on sustainability report disclosure. The population of this study consisted of 359 energy sector companies listed on the Indonesia Stock Exchange from 2019 to 2023, with 23 companies selected as samples, resulting in 57 observations. The sample was determined using a purposive sampling method and analyzed using multiple linear regression techniques. The results show that profitability and institutional ownership have no effect on sustainability report disclosure, while environmental performance has a positive effect on sustainability report disclosure. The theoretical implications of this study demonstrate the implementation of stakeholder theory in explaining the effect of environmental performance on sustainability report disclosure. This study also provides practical implications regarding the importance of sustainability report disclosure for companies as a form of corporate responsibility and commitment to sustainability, as well as providing information for investors in considering investment decisions.